What are the Behavioral Patterns of Students with Learning Disabilities during Science Lessons? - Kamsaeng, Chantakan (Journal of Teacher Professional Learning Community (JTPLC) (Online), 2025)
This research aims to examine the learning behaviors of a student with learning disabilities in a Grade 7 (Grade 7/2) Science 1 course at Nong No Prachasan School, under the Khon Kaen Provincial Administrative Organization. This qualitative study focused on interpreting the behavioral expressions of a single subject within the classroom. Initially, the student demonstrated a complete lack of interest and failed to participate in any tasks. Research instruments included the PLC002 learning observation form, student worksheets, and informal interviews. The findings reveal that the student’s behavior is significantly influenced by the social environment and the instructional design. When placed in a group where peers were indifferent or uncommunicative, the student remained passive and refused to interact with others, including the teacher. Conversely, when peers engaged the student in conversation, the student showed positive responses and attempted to complete assignments. Furthermore, applying scientific inquiry-based teaching methods effectively stimulated the student’s curiosity and engagement. This improvement was evidenced by the completion of workpieces and attempts to read assigned text-activities the student had previously refused to perform.